Engenharia genética como instrumento ao exercício do direito à felicidade - Guerra, Helena Carolina Gonçalves (2021)
This thesis aims to investigate whether there are connections amongst the right to happiness and the genetic manipulation of embryos. It addresses the importance of natural selection for the survival of species, the focal point of Darwin’s theory of evolution, as well as the means developed by human beings to improve their characteristics artificially and in a controlled way. After this introduction, it deals with the advances made in genetic engineering and the concerns that arose among scientists regarding the possibility of selecting the characteristics of an embryo. After this, the study will analyze the philosophical foundations upon which the theory of contemporary happiness is supported, in order to address how the right to happiness is inserted in the Brazilian legal system. Given these premises, due to lack of specific norms on the subject, this dissertation will analyze if bioethical principles allow a connection between the right to happiness and genetic manipulation of human embryos